Choosing between Muscle and Fasciocutaneous Free Flap Reconstruction in the Treatment of Lower Extremity Osteomyelitis: Available Evidence for a Function-Specific Approach - Kovar, Alexandra; Colakoglu, Salih; Iorio, Matthew L. (Journal of Reconstructive Microsurgery, 2020)
Background Limb salvage in the setting of extremity osteomyelitis, though previously dependent on amputation, has been markedly improved through the application of free tissue flaps. Concern exists as to the utility of the fasciocutaneous flap to combat infection verses the traditional muscle flap. Prior studies have shown success with fasciocutaneous flaps in these patients, but given the small series, the choice remains controversial. The goal of this article was to determine if there is statistical evidence for flap choice in the setting of extremity osteomyelitis.Methods A systematic review utilizing Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines was completed of the current literature pertaining to the treatment of extremity osteomyelitis and flap reconstruction within the MedLine and PubMed databases. Six hundred forty-six studies were reviewed and ultimately 31 were included in the final analysis.Results Eight hundred seventy-eight flap reconstructions were identified. Of the 588 muscle flaps, 7.8% (n = 46) had recurrence of osteomyelitis after an average of 36.1 (8.0–111.6) months follow-up. There were seven cases (4.3%) of osteomyelitis recurrence in the 163 fasciocutaneous flap group after an average of 29.8 (18.2–44.6) months follow-up (p = 0.165). Secondary outcomes such as flap loss, hematomas, and infection were analyzed without statistically significant differences between the muscle and fasciocutaneous flap groups.Conclusion Selection of flap type is less important than adequate debridement, appropriate antibiotic selection, and sufficient duration of treatment. This study demonstrates that within the literature, fasciocutaneous flaps have a lower recurrence rate of osteomyelitis compared with muscle flaps. As such, fasciocutaneous flaps are appropriate for reconstruction and treatment of extremity osteomyelitis.
Keywords: muscle flap; fasciocutaneous flap; osteomyelitis; extremities